ECONOMICS OF NITROGEN AND INTEGRATED WEED MANAGEMENT IN DRY SEEDED RICE - S. Ahmed; T. H. Awan M. Salim; B. S. Chauhan (Journal of Animal and Plant Sciences, 2015)
Dry-seeded rice (DSR) is an emerging production technology in many Asian countries, whose profitability is higher than puddled transplanted rice. However, weed infestations are severe in the DSR. To increase the competitiveness with weeds and achieve the yield potential of rice, weed management in DSR needs an integration of herbicides and higher nitrogen (N) fertilizer rates. Field experiments were conducted in the aman (wet season) 2012 and 2013 in Bangladesh to evaluate the effect of N rates (0, 80, 120, and 160 kg ha-1) and weed control methods [one hand weeding (HW); pendimethalin 1000 g ai ha-1 followed by (fb) ethoxysulfuron 20 g ai ha-1; pendimethalin fb ethoxysulfuron fb one HW; and weed-free] on weed growth and crop yield in DSR. The experiment was arranged in a split-plot design with three replications. The highest grain yield (5.3 to 5.5 t ha-1) was recorded in the season-long manual weed-free treatment when N rate was160 kg ha-1; however, because of the high cost of labor, this method was not profitable. The use of pendimethalin fb ethoxysulfuron fb one HW effectively controlled weeds and produced a similar yield with the weed-free treatment for all levels of N. However, weed management cost was also higher because of the involvement of one HW. Although pendimethalin fb ethoxysulfuron treatment had always lower yielded than the pendimethalin fb ethoxysulfuron fb one HW, grain yield increased and net profit was similar when N rate increased from 120 to 160 kg ha-1. Considering weed control efficiency, yield, and economics, pendimethalin fb ethoxysulfuron fb one HW with 120 kg N ha-1 may be recommended to growers. However, if laborers are not available for hand weeding, pendimethalin fb ethoxysulfuron with 160 kg N ha-1 is the best option to achieve high yield in DSR.
Keywords: Labor; manual weeding; herbicides; weed suppression; rice yield; resource conservation